PENGEMBANGAN MEDIA FLASHCARD “MITIGASI BENCANA ALAM” UNTUK MENGEMBANGKAN KREATIVITAS DAN KOMUNIKASI PESERTA DIDIK KELAS V SEKOLAH DASAR - Fatiya Sakinah; Yunimar Kholishah; Siti Fatonah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Flashcard media is a learning media that can help students understand their learning, especially in IPAS material. This study aims to analyze the feasibility of the "natural disaster mitigation" flashcard media by the validator and analyze the impact of the "natural disaster mitigation" flashcard media on students' creativity and communication. The research method used in this study is Research and Development with the ADDIE development model. The data collection technique used was in the form of observation sheets. The results obtained were the feasibility assessment of the "natural disaster mitigation" flashcard media that was developed and received an assessment from media experts with a percentage of 97%. Then, the assessment given by the two subject matter experts with percentages of 90% and 82%. Furthermore, the impact of creativity generated by students through the flashcard media "natural disaster mitigation" received a percentage result above 80% which was assessed through an observation sheet. The impact of communication is also seen through the acquisition of the existing percentage, which is in the range of 80%-85%. The impact of creativity and communication is shown through open-ended questions contained in the flashcard media "natural disaster mitigation". So, from the development of the "natural disaster mitigation" flashcard media carried out, it can be declared suitable for use in learning.